Analysis of Groundwater Flow on Hydrogeological for Sustainable Development and Environment in the Ternate Basin, North Maluku Province, Indonesia - Kadri Daud; Henny Pramoedyo; Aminudin Afandhi; Ishardita Pambudi Tama (Postgraduate School Universitas Brawijaya, 2022)
The sustainability of water and sanitation management is an important point in the 2021 SDGs program. To support the program, it is important to understand Indonesia's water cycle. Given the variety of characters, topography, and geology between islands in Indonesia can distinguish hydrogeological systems and their interactions with the surrounding environment. The design and management of water resources, especially groundwater, has an important role, considering the basin area is 106 km2, the character of a volcanic island with the name of an active volcano. Topography from 0-8% is a built-up zone, 8-14% is a cultivation zone, 14-45% is a protected forest, and >45% is a stratovolcano peak zone. Island morphology affects groundwater flow patterns. This study aimed to determine the characteristics of groundwater flow in the Ternate basin. Purposive sampling of 56 production wells, transmissivity value, conductivity, aquifer thickness, and topography was analyzed using the Cubic spline interpolation method. The results showed that the direction of flow and groundwater accumulation based on groundwater modeling using the kriging interpolation technique resulted in the interaction of groundwater flow and depression cones in 56 production wells due to the concentration and massive groundwater abstraction in the Ternate Basin. The decrease in groundwater level is fluctuating, from groundwater flows that occur radially-centrifugally, the total reserves of 56 production wells are 46 million m3/day, the average transmissivity value is 2.17 m2/day, production discharge is 51,710 m3/day.